2017
DOI: 10.1111/weng.12239
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual creativity in Saudi stand‐up comedy

Abstract: Stand‐up comedy is one of those art forms in which linguistic creativity can be seen in its most extravagant form, as stand‐up comedians mainly rely on their creative use of language to interact with their audience. This paper explores bilingual creativity in stand‐up comedy in Saudi English as an emerging variety. It investigates the form and function of bilingual creativity processes employed by Saudi comedians performing in English, and sets out to answer such questions as: What are the common forms of bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 60 publications
(93 reference statements)
5
20
0
Order By: Relevance
“…In this circle, English is socio‐politically imposed to be used and taught as a foreign language. Recent studies in the Saudi context showed an upcoming manifestation of using English with a Saudi flavor (Al‐Rawi, 2012; Alwzna, 2020; Bukhari, 2019; Fallatah, 2016, 2017; Mahboob, 2013; Mahboob & Elyas, 2014). Some studies which reported the existence of a ‘Saudi English’ remain inconclusive, lamenting the scarcity of literature on this local phenomenon.…”
Section: English In Saudi Arabiamentioning
confidence: 99%
See 2 more Smart Citations
“…In this circle, English is socio‐politically imposed to be used and taught as a foreign language. Recent studies in the Saudi context showed an upcoming manifestation of using English with a Saudi flavor (Al‐Rawi, 2012; Alwzna, 2020; Bukhari, 2019; Fallatah, 2016, 2017; Mahboob, 2013; Mahboob & Elyas, 2014). Some studies which reported the existence of a ‘Saudi English’ remain inconclusive, lamenting the scarcity of literature on this local phenomenon.…”
Section: English In Saudi Arabiamentioning
confidence: 99%
“…Many researchers reported an emerging ‘Saudi English’ and some of its features (Al‐Haq & Ahmed, 1994; Al‐Rawi, 2012; Alwznah, 2019; Bukahri, 2019; Fallatah, 2017; Mahboob & Elyas, 2014). However, Bukhari (2019) rejected the idea of ‘Saudi English’ and proposed the concept ‘Saudi ELF’ as the latter suggests the emergent use in transcultural contexts by users who project their complex identity management and negotiation regarding their English use.…”
Section: English In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…First, there are a growing number of studies over the past five years that offer glimpses of the burgeoning of localized forms of Englishes in the region. The stage is either set or already at the ‘nativization’ phase (Schneider, 2003, 2007) for postcolonial English varieties (Al‐Rawi, 2012; Al‐Surmi, 2018; Boyle, 2012, 2014; Dashti, 2015; Fallatah, 2017; Mahboob & Elyas, 2014); this is especially the case in the Arabian Peninsula where expatriate populations coming predominantly from South and Southeast Asia outnumber citizens. Given the large percentage of expatriates, local Englishes in the Arabian Peninsula are not only influenced by Inner Circle Englishes (Kachru, 1985, 1992a) but also other Expanding and Outer Circle Englishes, predominantly Indian Englishes (Buckingham, 2015b; Poole, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…There has also been a tendency to discuss the status of English predominantly in educational, business, and media spheres. Fallatah's (2017, p. 681) study of bilingual creativity in Saudi stand‐up comedy provides a good example of how to take the research further, by closely analyzing features of English in a specific genre related to pop culture and how Saudis are ‘using English as a convenient tool to represent Saudi culture and to express itself to the rest of the world.’ Now that we have some broad overviews of many of the countries in the MENA region, it would be useful to more closely examine empirical data like discourse/genre/pragmatics/rhetoric and how they interact with larger language ideologies and global discourses (Hawkins, 2008). More longitudinal, ethnographic approaches to examining WE in the MENA region could also provide a deeper richness to our understanding of the roles, statuses, and functions of Englishes.…”
Section: Discussionmentioning
confidence: 99%